Management of Supracondylar Fractures of the Humerous in Children - Asghar Khan, Sayed Sohail Akhtar, Saeed Ahmad, Abdul Rauf Tippu, Nadeem Qureshi, Sartaj Lakhani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Supracondylar humeral fractures (SFH) are the most common fractures of the pediatric elbow, having a peak frequency between the ages of four and nine years. The majority of surgical therapy is percutaneous pinning and closed reduction. The present study aimed to determine the outcome of close reduction and percutaneous pinning in managing the supracondylar humeral fractures in children. Patients and Methods: A total of 64 children presented with supracondylar humeral fractures to the Orthopaedics Unit of Bacha Khan Medical Complex, Swabi during the period from 16th February 2022 to 15th November 2022. Children with supracondylar humerus fractures of completely displaced (Gartland Type III) were enrolled whereas neurovascular injury related to open or closed Gartland type-III fracture were excluded. Under general anesthesia, close reduction was accomplished, and the elbow was immobilized in extension by the implantation of two plaster slabs. The type of fracture, injury pattern, time from injury to final therapy, surgical treatment, and consequences were all recorded. Results: The overall mean age was 4.89±3.2 years. Of the total 64 SFH cases, there were 52 (81.3%) male and 12 (18.7%) females. Out of 52 (81.3%) children with pulseless hands, the incidence of Gartland type III and IV was 15.4% (N=8) and 84.6% (N=44) respectively. Out of 52 cases, there were 19 (36.5%) cold hands and 33 (53.5%) warm hands. The overall mean time between injury and presentation was 3.8±2.4 hours. The incidence of patients undergoing autologous interposition venous grafting, vascular reconstruction, and segmental resection and primary anastomosis was 25% (N=16), 59.4% (N=38), and 15.6% (N=10) respectively. There were no amputations, fasciotomies, re-explorations, or long-term ischemic sequelae. Conclusion: The present study found that close reduction and immobilization with two slabs is a safer and effective method for superior outcome of managing supracondylar humeral fractures in uncomplicated type III injuries as compared to flexion approach. Additionally, Rapid vascular exploration might effectively treat both cold and warm pulseless hands. Keywords: Supracondylar humeral fractures, Management, Children, Close reduction approach